2002
DOI: 10.1002/jsfa.1178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative content of some phytochemicals in Spanish apples, peaches and pears

Abstract: Dietary fibre, total polyphenols and phenolic acids in Spanish apples, peaches and pears were analysed and compared with their total radical-trapping antioxidative potential (TRAP). There were no significant differences in the content of dietary fibre among the studied fruits. The content of total polyphenols was 2.4 AE 0.4, 2.1 AE 0.3 and 6.9 AE 0.7 g kg À1 in peeled fruits and 4.7 AE 0.4, 4.5 AE 0.4 and 11.1 AE 1.2 g kg À1 in their peels for peaches, pears and apples respectively. The contents of dietary fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 25 publications
1
44
4
2
Order By: Relevance
“…Sun et al, (2002) extracted fruit in 80% acetone followed by base digestion and ethyl acetate extraction, while Gardener et al, (2000) centrifuged the juice before estimating the total phenolic content. Extraction of crude polyphenols using aqueous methanol/ethanol or acetone is quite popular and frequently done (Gorinstein et al, 2002;Larrauri et al, 1997). The concentrations of solvent used also have impact on the amount of phenolic extracted.…”
Section: Utilization Of Pineapple Wastementioning
confidence: 99%
“…Sun et al, (2002) extracted fruit in 80% acetone followed by base digestion and ethyl acetate extraction, while Gardener et al, (2000) centrifuged the juice before estimating the total phenolic content. Extraction of crude polyphenols using aqueous methanol/ethanol or acetone is quite popular and frequently done (Gorinstein et al, 2002;Larrauri et al, 1997). The concentrations of solvent used also have impact on the amount of phenolic extracted.…”
Section: Utilization Of Pineapple Wastementioning
confidence: 99%
“…Several investigations have shown that fruits are a natural source of dietary fiber, trace elements and antioxidant compounds, and that diets rich in fruits positively influenced plasma lipid levels and antioxidant capacities in experiments with laboratory animals GORINSTEIN et al, 2002;LEONTOWICZ et al, 2001;LEONTOWICZ et al, 2002). Boyer and Liu (2004) found that the total antioxidant activity of apples with their peel was approximately 83 µmol vitamin C equivalents, which means that the antioxidant activity of 100 g apples is equivalent to about 1500 mg of vitamin C.…”
Section: Vitamin C/phenolic Compounds/tanninsmentioning
confidence: 99%
“…The positive influence of these natural products is attributed to their bioactive compounds: dietary fiber and antioxidants, mainly phenolic compounds, flavonoids, phenolic acids (Gorinstein et al, 2002;Alothman et al, 2009). As it has been shown, diets rich in dietary fiber and other bioactive substances have decreased the risk of diseases such as coronary atherosclerosis, obesity and cancer (Rimm et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Various solvent systems have been used for the extraction of polyphenols from plant materials. Water and aqueous mixture of ethanol (Gorinstein et al, 2002), methanol (Orazem et al, 2011;Manzoor et al, 2012a) and acetone (Hamauzu et al, 2006) are commonly used. Alothman et al (2009) reported that aqueous acetone was superior to methanol and ethanol in the extraction of phenols from fruits.…”
Section: Introductionmentioning
confidence: 99%